Cation/Anion substitution into spinel LiMn2O4 cathode material for Li-ion battery application: a review of recent progress - Zahoor, Ahmed; Liew, Josephine Ying Chyi; Talib, Zainal Abidin (The Electrochemical Society, 2021)
Spinel LiMn2O4 is a positive electrode material with a robust structure. It has a three-dimensional network of channels for fast lithium-ion diffusion in state-of-the-art lithium rechargeable batteries. It is commercialized because of its high-power and cost-effective natural abundant element. However, its capacity fading and cycle performance, originating from Mn dissolution, still need improvement. In this review, the recent development of the effect of cation and anion doped into the spinel LiMn2O4 cathode material is thoroughly investigated. The effect of anion substitution on the morphology and electrochemical properties were investigated. Cation/anion substitution shows improvement in the structural stability and suppresses lattice deformation of the material. Finally, some insight into the future prospects for spinel cathode developments is provided.